ANALYSIS OF FACTORS INFLUENCING DECISIONS TO PURCHASE HALAL LABELED FACIAL FOAM FOR MEN PRODUCTS (STUDY IN SERANG CITY COMMUNITIES) - Haryati, Sri; Wazin, Wazin; Peristiwo, Hadi (Universitas Mathla’ul Anwar Banten, 2023)
The Indonesian cosmetics industry is currently experiencing very rapid development so that this situation has given rise to competitive and tight business competition. Even though the majority of the cosmetics industry targets women as its main consumer target, it has recently begun to innovate with products for men. Currently, the halal trend is receiving special attention in society, including cosmetics in the form of facial foam products for men which are labeled halal. There are several factors that influence consumer purchasing decisions in purchasing halal products, including halal labeling, brand image, product quality and also product price. The method used in this research is quantitative research with a descriptive approach because the data used is in the form of numbers which are then processed using statistical methods. Based on research results It was concluded that halal labeling, product quality, product price and brand image simultaneously influence purchasing decisions. This is proven by the calculated F test results of 1 9.388 with an F significance of 0.000, so it can be concluded that the four independent variables simultaneously have an influence significant to the dependent variable. However, halal labeling and product price partially influence it, but product quality and brand image do not partially influence the decision to purchase facial foam products for men labeled halal in Serang City.